Autoimmune Regulator (AIRE) Deficiency Does Not Affect Atherosclerosis and CD4 T Cell Immune Tolerance to Apolipoprotein B - Nettersheim, Felix Sebastian; Braumann, Simon; Kobiyama, Kouji; Orecchioni, Marco; Vassallo, Melanie; Miller, Jacqueline; Ali, Amal; Roy, Payel; Saigusa, Ryosuke; Wolf, Dennis; Ley, Klaus; Winkels, Holger (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is a chronic, lipid-driven disease of medium sized arteries which causes myocardial infarction and stroke. Recently, an adaptive immune response against the plaque-associated autoantigen Apolipoprotein B100 (ApoB), the structural protein component of low-density lipoprotein, has been implicated in atherogenesis. In healthy individuals, CD4+ T cells responding to ApoB mainly comprised regulatory T cells, which confer immune tolerance and atheroprotection. Mice and patients with atherosclerosis harbor increased numbers of proatherogenic ApoB-reactive T-helper cell subsets. Given the lack of therapies targeting proatherogenic immunity, clarification of the underlying mechanisms is of high clinical relevance. T cells develop in the thymus, where strong autoreactive T cells are eliminated in the process of negative selection. Herein, we investigated whether the transcription factor autoimmune regulator (AIRE), which controls expression of numerous tissue-restricted self-antigens in the thymus, is involved in mediating tolerance to ApoB and whether Aire deficiency might contribute to atherogenesis. Mice deficient for Aire were crossbred to apolipoprotein E-deficient mice to obtain atherosclerosis-prone Aire−/−Apoe−/− mice, which were fed a regular chow diet (CD) or western-type diet (WD). CD4+ T cells responding to the ApoB peptide p6 were analyzed by flow cytometry. We demonstrate that Aire deficiency influences neither generation nor activation of ApoB-reactive T cells and has only minor and overall inconsistent impacts on their phenotype. Furthermore, we show that atherosclerotic plaque size is not affected in Aire−/−Apoe−/− compared to Aire+/+Apoe−/−, irrespective of diet and gender. In conclusion, our data suggests that AIRE is not involved in regulating thymic expression of ApoB or atherosclerosis. Alternative mechanisms how ApoB-reactive CD4 T cells are selected in the thymus will have to be investigated.